Literary Culture in Early Modern England, 1630-1700 Angles of Contingency - Berensmeyer, Ingo (De Gruyter, 2020)
This book explores literary culture in England between 1630 and 1700, focusing on connections between material, epistemic, and political conditions of literary writing and reading. In a number of case studies and close readings, it presents the seventeenth century as a period of change that saw a fundamental shift towards a new cultural configuration: neoclassicism. This shift affected a wide array of social practices and institutions, from poetry to politics and from epistemology to civility.